Mutations in the SPINK1 gene in idiopathic pancreatitis Italian patients - Gomez-Lira, Macarena; Bonamini, Deborah; Castellani, Carlo; Unis, Lorenza; Cavallini, Giorgio; Assael, Baroukh Maurice; Pignatti, Pier Franco (European journal of human genetics : EJHG, 2003)
Idiopathic chronic and acute recurrent pancreatitis (IP) have been associated with mutations in the cystic fibrosis transmembrane conductance regulator ( CFTR ) gene. Mutations in the serine protease inhibitor Kazal 1 ( SPINK1 ) have been described in some idiopathic chronic patients and it has been suggested that mutations in this gene could be responsible for a loss of trypsin inhibitor function. In this study, the 5′UTR region, and the four exons and exon–intron boundaries of the SPINK1 gene in 32 IP patients have been analyzed. Three IP patients (9.3%) and one control/100 carried the N34S mutation of the SPINK1 gene (Fisher's exact test, P =0.044). No other mutation that could be associated with an altered function of the SPINK1 protein was observed. The N34S mutation was present in two patients who carried the CFTR-IVS8 5T variant and in one who carried the L997F variant in the CFTR gene. The association of SPINK1 with CFTR gene mutations in IP patients is statistically significant (3/32 IP cases and 0/100 control individuals carrying mutations in both genes; Fisher's exact test P =0.01).